A Peep into the Sources of Policy Implementation Inertia in Africa: The Case of the Matabeleland Zambezi Water Project (MZWP) in Zimbabwe - GIDEON, Zhou; ALOUIS, Chilunjika (Asian Journal of Empirical Research, 2013)
A century has passed since the idea of solving the chronic water woes of Bulawayo and Matabeleland region by constructing a 450km water pipeline from the Zambezi River to Bulawayo was initiated in 1912. The Project, when conceptualized, was expected to spur socioeconomic growth by creating a green belt of agricultural projects in the region. To date, the Project is yet to come to fruition. This study sought to unravel factors accounting for this policy inaction, drawing from implementing experiences in Africa and across the world. The study revealed a series of interlocking factors relating to the nature of the project, legal hitches, fiscal incapacity, and regionalization of the Project, among others. The bilateral route recently adopted by Government should be vigorously pursued. Government should also mobilize local funds through local public-private sector arrangements.